Dinamika Dan Perkembangan Peraturan Pada Masa Pandemi Covid 19 Dalam Perspektif Tanggung Jawab Negara - Sudjana (KRTHA BHAYANGKARA, 2021)
Handling the Covid 19 pandemic through statutory policies is a liability that needs to be implemented in the concept of a welfare state but needs to be supported by active community participation. The approach method used is normative juridical and juridical empirical, data collection techniques are derived from secondary data, and data analysis is normative qualitative. The results of the study show that the liability of the State through statutory policies in stages in handling the Covid 19 pandemic has been implemented according to the concept of a welfare state because the state has undertaken an obligation to fulfill its character in providing special protection, so that it becomes the source of all laws and regulations in social affairs. However, efforts to fulfill the State's liability are associated with the legal system, according to Friedman, which is still constrained by the low legal culture of society in adhering to it.